The great Indian privity trick: hundred years of misunderstanding nineteenth century English contract law. (2nd January 2016) - Swaminathan, Shivprasad
ABSTRACT: It has been the received wisdom for over a century now that the Indian Contract Act 1872 could not have meant to alter the English law's privity requirement as there is no specific language dispensing with the privity rule. In the 1860s, when the Act was being drafted, however, a person from whom consideration did not move did not have the right to sue at English law. This was the only barrier the drafters envisaged and dismantled with s 2(d), which allowed consideration to move from the 'promisee' or 'any other person'. But its effect was also to preempt any putative privity of contract based barrier; as long as the promisor got the desired consideration, not only the 'promisee' but 'any other person'—whether or not a party—could sue upon the contract.